KEBIJAKAN PENGECUALIAN PAJAK DIVIDEN: KABAR BAIK ATAU BURUK BAGI INVESTOR - Indah Shofiyah; Aryan Danil Mirza. BR; Cornelius Saryadi Turnip; Ayu Nani Djismudin; Raihan Razif Afero; Nasrul Maulana (Faculty of Economics and Business, 2023)
The issuance of Omnibus Law Policy is predicted to be an effective policy in simplifying regulations, especially in the field of taxation. This study aims to find out in depth the perceptions of various parties regarding the implementation of PMK No. 18 regarding Exceptions from the Imposition of Income Tax on Dividends. Researchers try to map the problem from various perspectives, including investors, securities companies, tax consultants, tax officials and academics. The research was conducted using a qualitative approach with structured interview techniques. The results show that this Exemption of Dividend Tax policy is beneficial for corporate taxpayers, while for personal taxpayers it still tends to be detrimental because the administration is too complicated. So that policy makers need to review the implementation of Minister of Finance Regulation. In addition, the results of the study also show that although in the short term this policy has the potential to reduce Government revenues from the tax sector, in the long term this policy has the potential to accelerate national economic growth, especially after the Covid-19 pandemic. This research can be a reference for the government and academics in implementing policies in the field of taxation.